Band Gap Dependence on Cation Disorder in ZnSnN2 Solar Absorber. Issue 24 (29th October 2015) - Veal, Tim D.; Feldberg, Nathaniel; Quackenbush, Nicholas F.; Linhart, Wojciech M.; Scanlon, David O.; Piper, Louis F. J.; Durbin, Steven M.
Abstract : The band gap of earth‐abundant ZnSnN2 can be tuned between 1 and 2 eV by varying the growth conditions and resulting cation disorder. The optical absorption edges and carrier densities fall between model curves for cation‐ordered orthorhombic and disordered wurtzite ZnSnN2 . Hard X‐ray photoemission spectra suggest different degrees of cation disorder from comparison with hybrid DFT‐calculated densities of states.